New methods to detect early manifestations of adverse side effects of glucocorticosteroids in children - Galina A. Batishcheva; Olga A. Zhdanova; Tatiana L. Nastausheva; Natalia Y. Goncharova; Yuri N. Chernov (Belgorod National Research University, 2018)
Introduction: The article focuses on the early manifestations of adverse side effects in children with nephrotic syndrome receiving glucocorticosteroids. The search for criteria of early side effect manifestations is a real challenge nowadays. The authors developed new diagnostic criteria for early detection of pharmacotherapeutical side effects in children with nephrotic syndrome. Objective: The aim of the study was to develop integral quantitative diagnostic criteria for early detection of side effects of glucocorticosteroids when treating nephrotic syndrome in children. Materials and Methods: The study included 58 in-patients, aged 1-18. All the children had been thoroughly examined and their parameters had been investigated: height and body mass by calculating Z-scores (WHO ANTHRO Plus) and body mass index (BMI), a biochemical blood test, a full blood count by studying the total number of leukocytes, the percentage of neutrophils and monocytes in peripheral blood, systolic and diastolic blood pressure. Results and Discussion: The parameters that changed in the patients with nephrotic syndrome taking corticosteroids are referred to as diagnostic criteria. They included leukocytes, neutrophils and monocytes parameters in the full blood count, blood glucose and amylase level, patients' body mass, BMI, systolic and diastolic arterial pressure. The authors defined the change range of the parameters under study in the children with nephrotic syndrome based on the obtained findings. Conclusion: The authors conclude that application of the developed indices will make it possible to diagnose early metabolic, cardio-vascular and immunologic changes in patients with nephrotic syndrome taking glucocorticoids and perform their individual pharmacological correction in a timely manner.